What Drives CSR? An Examination of Slack Resources, Corporate Governance, and External Factors - Zahra Raisa Putri; Hidayati Nasrah (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2026)
Purpose: This study examines the impact of slack resources, corporate governance proxied by board size and institutional ownership, growth, and media exposure on corporate social responsibility within the mining sector, a sector that frequently encounters issues related to environmental damage caused by its operational activities. Method: This study employs panel data regression analysis using Eviews 12. Through purposive sampling, 50 mining companies were selected from a population of 81 for the 2022–2024 research period. Results: The findings indicate that slack resources, board size (as a proxy for corporate governance), and media exposure positively impact corporate social responsibility. In contrast, institutional ownership (as a proxy for corporate governance) and growth show no significant relationship with it. Implications: The findings of this research can assist company management, particularly in the mining sector, in making decisions related to resource allocation. In addition, the findings can be useful in promoting corporate transparency and accountability, particularly in the mining sector, which is sensitive to social and environmental issues. Novelty: As a sector that often faces social and environmental issues, mining was selected as the new focus for this research. Furthermore, it introduces slack resources as a new variable and replaces the corporate governance variable proxy with board size and institutional ownership.